2013
DOI: 10.1029/gm124p0099
|View full text |Cite
|
Sign up to set email alerts
|

Gas Hydrate-Associated Carbonates and Methane-Venting at Hydrate Ridge: Classification, Distribution, and Origin of Authigenic Lithologies

Abstract: plex of the Cascadia margin in 1984 [Suess et al., 1985;Kulm et al. 1986;Ritger et al., 1987]. Due to the observa tion of active methane ebullition [Linke et al. 1994], the documentation of a well-developed bottom simulating re flector (BSR) [Westbrook et al, 1994;Trehu et al, 1999], and the recovery of carbonates and gas hydrate at ODP-Site 892 , Hydrate Ridge (Fig. 1) became the focus of intense investigations of GEOMAR Research Center during RV SONNE cruises SO109 and SOI 10 in 1996. One goal of this intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
222
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(239 citation statements)
references
References 23 publications
12
222
4
1
Order By: Relevance
“…Almost all modern marine environments with gas hydrates develop seep carbonates [44][45][46][47]. This phenomenon mirrors the close relationship between gas hydrates and seep carbonates.…”
mentioning
confidence: 94%
“…Almost all modern marine environments with gas hydrates develop seep carbonates [44][45][46][47]. This phenomenon mirrors the close relationship between gas hydrates and seep carbonates.…”
mentioning
confidence: 94%
“…The overall reaction of combined AOM and sulphate reduction increases alkalinity, promoting the precipitation of authigenic carbonate 12 . An estimated 14% of biologically oxidized methane at active seep settings precipitates in this manner 13 , leading to a range of carbonate minerals 14 . The resulting precipitation products may vary in size, ranging from microcrystals 15 to extensive structures of pavements, slabs and mounds produced by upward growth (known as chemoherms) or post-formation winnowing 14,16,17 .…”
mentioning
confidence: 99%
“…An estimated 14% of biologically oxidized methane at active seep settings precipitates in this manner 13 , leading to a range of carbonate minerals 14 . The resulting precipitation products may vary in size, ranging from microcrystals 15 to extensive structures of pavements, slabs and mounds produced by upward growth (known as chemoherms) or post-formation winnowing 14,16,17 . Carbonate volumes have been estimated for a few regions of active seepage and may exceed a million cubic metres at areas such as the Costa Rica margin 4 , Hydrate Ridge 6 and the Chilean subduction zone 5 , suggesting that these methane-derived structures have the potential to serve as a significant habitat within the seep ecosystem.…”
mentioning
confidence: 99%
“…Nevertheless, the precipitation of aragonite and calcite seems to be favored in more oxic environments with both high sulphate concentration and alkalinity. On the other hand, the crystallization of Mg-calcite and dolomite preferentially occur under slightly more anoxic conditions, with lower SO 4 2-content as well as a lower total alkalinity (Greinert et al 2001), conditions observed in freshwater lakes. The presence of manganese carbonate cement within ostracode shells would corroborate this assumption.…”
Section: Vesicles Formationmentioning
confidence: 99%